Identification of Aquifer Potential Using Electrical Resistivity Tomography (ERT) Method in the Karst Area of Giritontro, Wonogiri, Central Java - Nadia Putri Nur Asri; Rahma Puspa; Anggara Putra Prasetya; Budy Santoso (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Karst regions exhibit unique geological characteristics due to the dissolution of carbonate rocks, lending to the formation of complex underground aquifer systems. This study was conducted in BayemharjoVillage, Giritontro Sub-district, Wonogiri Regency part of the Sewu Karst Zone to identify aquifer potential using the dipole dipole electrical resistivity method. The survey was carried out along three measurement lines ranging from 216 to 710 meters in length, utilizing 72 electrodes with 10 meter spacing. The research involved data acquisition, processing, and interpretation using specialized resistivity software. Interpretation result revealed rock layers with potential as aquifers, particulary those with porous and permeable lithologies such as sandy limestone. Additionally, the presence of aquitard and aquiclude layers was identified, acting as barriers or flow paths for groundwater movement. The resistivity patterns and geological structures indicate the existence of groundwater pockets at various depths, which are crucial for managing clean water resources in this drought-prone region. The resistivity method prove to be effective in delineating aquifers zone within the complex karst environment.